Indigenous archaeologies : decolonizing theory and practice - Smith, Claire, 1957-; Wobst, Hans Martin, 1943- (London ; New York : Routledge, 2005)
With case studies from North America to Australia and South Africa and covering topics from archaeological ethics to the repatriation of human remains, this book charts the development of a new form of archaeology that is informed by indigenous values and agendas. This involves fundamental changes in archaeological theory and practice as well as substantive changes in the power relations between archaeologists and indigenous peoples. Questions concerning the development of ethical archaeological practices are at the heart of this process.
Decolonizing archaeological theory and practice -- Power to the (indigenous) past and present! : or, the theory and method behind archaeological theory and method -- Indigenous worldviews and ways of knowing as theoretical and methodological foundations for archaeological research -- Developing an aboriginal archaeology : receiving gifts from White Buffalo Calf Woman -- Earthshapers and placemakers : Algonkian Indian stories and the landscape -- The persistence of memory, the politics of desire : archaeological impacts on aboriginal peoples and their response -- You write it down and bring it back, that's what we want : revisiting the 1948 removal of human remains from Kunbarlanja (Oenpelli), Australia -- Letters from the field : reflections on the nineteenth-century archaeology of Harlan I. Smith in the southern interior of British Columbia, Canada -- Reclaiming the ancient one : addressing the conflicts between American Indians and archaeologists over protection of cultural places -- The politics of American archaeology : cultural resources, cultural affiliation and Kennewick -- Silencing and sharing of southern African indigenous and embedded knowledge -- Aboriginal ecotourism and archaeology in coastal NSW, Australia : Yarrawarra Place Stories Project -- Kungun Ngarrindjeri Yunnan : archaeology, colonialism and re-claiming the future -- Coming back to country : a conversation at Firewood Creek -- Not just black and white : African Americans reclaiming the indigenous past -- First, be humble : working with indigenous peoples and other descendant communities -- We just have to show you : research ethics blekbalawei -- Living and learning on aboriginal lands : decolonizing archaeology in practice -- Looking forward -- looking back : shaping a shared future -- Towards an indigenous research charter -- The next step : an archaeology for social justice.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Ethnoarchaeology; Social archaeology; Indigenous peoples -- Antiquities; Archaeology -- Philosophy; Archaeologists -- Professional ethics; Archaeology -- Fieldwork; Human remains (Archaeology) -- Repatriation; Cultural property -- Repatriation; Ethnoarchéologie.; Archéologie sociale; Autochtones -- Antiquités.; Archéologie -- Philosophie; Archéologues -- Déontologie.; Archéologie -- Recherche sur le terrain; Restes humains (Archéologie) -- Rapatriement; Patrimoine culturel -- Restitution; ethnoarchaeology; SOCIAL SCIENCE -- Archaeology; Indigenous peoples -- Antiquities; Archaeologists -- Professional ethics; Archaeology -- Fieldwork; Archaeology -- Philosophy; Cultural property -- Repatriation; Ethnoarchaeology; Human remains (Archaeology) -- Repatriation; Social archaeology; Ethnoarchäologie; Ethnoarchéologie -- Congrès.; Archéologie sociale -- Congrès.; Autochtones -- Antiquités -- Congrès.; Archéologie -- Philosophie -- Congrès.; Archéologues -- Déontologie -- Congrès.